Proactive Versus Reactive Seismic Monitoring in Mines - Results of a Seismic Monitoring Survey - Hudyma, MR; Heal, D (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
A survey was undertaken to examine the use of seismic monitoring in mines. The 20-question survey titled “Application of Seismic Monitoring” (ASM) was used for rating the design and operation of seismic systems, and the application of seismic data. The survey indicated that the design, operation and data processing is relatively well conducted at most mines. However, data analysis and data interpretation are often not as well undertaken. Possible reasons for the lack of data analysis and data interpretation could be: lack of acceptance of mine seismology techniques, insufficient training, inadequate analysis tools, or lack of time to conduct the analyses. Mines that score well on the ASM survey tend to use their seismic systems proactively to understand the seismicity problem in their mines. Mines that score below average on the ASM survey tend to use seismic monitoring almost entirely as a reactive tool. The survey results for the 33 mines have been summarised to provide a means of benchmarking site practice against general practice in Australia and Canada.